Serum osteopontin in patients with lung cancer and chronic obstructive pulmonary disease: does the co-existence make the difference? - Petta, Vasiliki; Loukides, Stelios; Kostikas, Konstantinos; Papaioannou, Andriana I.; Papatheodorou, Georgios; Cholidou, Kyriaki; Tomos, Ioannis; Papiris, Spyridon; Koulouris, Nikolaos G.; Bakakos, Petros (Journal of Thoracic Disease; Vol 10, No 2 (February 14, 2018): Journal of Thoracic Disease, 2018)
Background: Osteopontin (OPN) is involved in cancer development and metastasis. Increased sputum OPN was detected in chronic obstructive pulmonary disease (COPD). Methods: We evaluated serum OPN levels in patients with lung cancer (LC) and/or COPD and aimed to determine OPN prognostic performance in 1-year mortality in LC and also its diagnostic performance in LC among COPD patients. We recruited 167 LC patients, 85 with concomitant COPD. 28 COPD patients served as control group. Results: OPN levels were higher in LC compared to COPD alone (P=0.017) and higher in COPD and LC compared to COPD alone (P=0.031). No difference was observed in OPN levels between LC and COPD vs. LC without COPD (P=0.171). Serum OPN ≥50.3 ng/mL was an independent predictor of 1-year mortality in LC. Conclusions: OPN levels ≥35 ng/mL could predict the presence of LC among COPD patients. In patients with LC and/or COPD, LC is the major determinant for serum OPN. Serum OPN might be a promising prognostic biomarker of LC and a diagnostic biomarker of LC among COPD patients.